Promised land - Damon, Matt.; Krasinski, John.; McDormand, Frances (Universal City, CA : Universal Studios, 2013)
Corporate salesman Steve Butler has been dispatched to the rural town of McKinley with his sales partner to offer much-needed relief to the economically hard-hit residents in exchange for drilling rights to their properties. What seems like an easy job for the duo quickly becomes complicated by a respected schoolteacher, a slick environmental activist, and Steve's interest in a local woman. As they grapple with a surprising array of both open hearts and closed doors, the outsiders soon discover the strength of an American small town at a crossroads.
Bonus features: Extended scene - The making of Promised Land.
MPAA rating: R for language.